Colloidal Quantum Dot Image Sensors: Technology and Marketplace Opportunities. (29th November 2021) - Goossens, Stijn; Konstantatos, Gerasimos; Oikonomou, Antonios
Abstract: CQD image sensor technology is a promising platform that enables the emergence of widespread advanced computer vision applications.